PENERAPAN SISTEM INFORMASI SURAT MASUK DAN SURAT KELUAR PADA SMA NEGERI 1 SUNGAYANG KECAMATAN SUNGAYANG KABUPATEN TANAH DATAR - Ricky Akbar; Jefril Rahmadoni (Jurnal Hilirisasi IPTEKS, 2023)
The goal of this activityis to create an information system for incoming and outgoing letters that will help the school manage letters administration. So far, the process of managing incoming and outgoing letters at SMA Negeri 1 Sungayang, Tanah Datar Regency, West Sumatra, is still done conventionally and manually, where the process of making incoming and outgoing letters uses MS. Office (Word Processing), which, of course, is not stored in a database archive, and the school will find it difficult later to find a letter file that has been made and is very vulnerable to being damaged by viruses or the like. Meanwhile, for the process of recording and managing each incoming letter, use a ledger made in a specific format to record numbers or other information from the letters. This is also inefficient because it requires a large amount of paper, which is prone to damage or loss of archives. To accomplish this, we require an information system capable of automatically creating and managing incoming and outgoing mail and storing it in a database. The method used in building this application is the waterfall system development method. One of the applications of the incoming and outgoing mail information system is training, which is held at SMA Negeri 1 Sungayang with the participants being operators and administrative staff. The outcomes of this training activity are expected to be that the operators and administrative staff who manage incoming and outgoing letters at SMA Negeri 1 Sungayang understand how to operate the application, allowing the application for incoming and outgoing letters to be well operationalized at SMA Negeri 1 Sungayang later, that way the school can create and manage incoming and outgoing letters to be more effective, efficient and automated.